Pros and Cons of Donor Breast Milk Versus Formula Milk for Premature and LBW Babies - Vernando Yanry Lameky; Nastain Abubakar Pattimura; Bazrul Makatita (Knowledge Dynamics, 2024)
Feeding premature and low birth weight (LBW) babies requires careful consideration due to their heightened vulnerability. Donor breast milk offers essential nutrients, antibodies, and beneficial bacteria, reducing the risk of infections and promoting healthy gut microbiota. However, accessibility and cost constraints pose challenges for many families. Formula milk provides a convenient alternative but lacks the immune-boosting properties of breast milk and may increase the risk of digestive problems and metabolic diseases later in life. Informed decision-making is crucial, considering both short-term benefits and long-term risks. Further research and support are needed to ensure optimal nutrition for premature and LBW babies, empowering parents and healthcare providers alike.Keywords: Premature babies; low birth weight babies; donor breast milk; formula milk